The Effects of ZIS, Poverty, and Unemployment Rates on the Human Development Index in West Java (Before and During the COVID-19 Pandemic, 2018–2022) - Wardana, Rifa Aqil Adifa; Anas Budiharjo (Islamic Economics and finance in Focus, 2026)
This study aims to analyze the effect of Zakat, Infak, and Sedekah (ZIS), poverty, and unemployment rates on the Human Development Index (HDI) before and during the COVID-19 pandemic from 2018 to 2022 using panel data from 27 districts in West Java. The research method used in this study is quantitative with a Fixed Effect Model (FEM) panel data regression analysis method using secondary data obtained from the Central Statistics Agency (BPS) and the National Zakat Agency (BAZNAS). The results of this study indicate that ZIS has a positive and significant effect on the Human Development Index in West Java. In addition, poverty and unemployment rates have a negative and significant effect on the HDI. Furthermore, the COVID-19 dummy variable shows a difference in HDI achievement between the pre-pandemic and pandemic periods. The results of this study are expected to serve as a reference for local governments and policy makers in formulating strategies to improve human development through the optimization of ZIS and the control of poverty and unemployment, so that the HDI in West Java can increase sustainably.   Keywords: ZIS; Human Development Index; Poverty; unemployment